2019
DOI: 10.1073/pnas.1900338116
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-186-5p controls GluA2 surface expression and synaptic scaling in hippocampal neurons

Abstract: Homeostatic synaptic scaling is a negative feedback response to fluctuations in synaptic strength induced by developmental or learning-related processes, which maintains neuronal activity stable. Although several components of the synaptic scaling apparatus have been characterized, the intrinsic regulatory mechanisms promoting scaling remain largely unknown. MicroRNAs may contribute to posttranscriptional control of mRNAs implicated in different stages of synaptic scaling, but their role in these mechanisms is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 89 publications
2
49
0
Order By: Relevance
“…According to the literature, miR-375 is relevant to psychiatric conditions and psychological phenotypes ( Bhinge et al., 2016 ; Dulcis et al., 2017 ), while chronic unpredictable stress can cause miR-375 increase thus affecting expression of relevant genes ( Lotan et al., 2018 ). In turn, the role of miR-186 in synaptic scaling as a degree of stable neuronal activity affected by developmental processes was demonstrated ( Silva et al., 2019 ). Therefore, future research on the connection between rs3803107 variations and depression liability via miR-375 and miR-186 binding appears to be promising.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, miR-375 is relevant to psychiatric conditions and psychological phenotypes ( Bhinge et al., 2016 ; Dulcis et al., 2017 ), while chronic unpredictable stress can cause miR-375 increase thus affecting expression of relevant genes ( Lotan et al., 2018 ). In turn, the role of miR-186 in synaptic scaling as a degree of stable neuronal activity affected by developmental processes was demonstrated ( Silva et al., 2019 ). Therefore, future research on the connection between rs3803107 variations and depression liability via miR-375 and miR-186 binding appears to be promising.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that constant a-and c-tDCS form a downward and an upward current flow along axons of neurons arranged in vertical columns, respectively (Lund et al 2003;Douglas & Martin, 2004;Ohki et al 2005), which may preferentially affect the synthesis of neurotransmitters and thus produce directionally specific neurophysiology changes (Hannah et al 2019). For example, current flow in varied directions may differently affect the transmembrane transportation of Ca 2+ (Brosenitsch & Katz, 2001), which will initiate specific genes expression by activation of its transcription factors (Hardingham et al 1998;Ma et al 2014;Fukuchi et al 2015;Puri, 2020) or suppress some genes expression through microRNA-mediated post-transcriptional silence (Lee et al 2012;Rajgor et al 2017;Wan et al 2018), including the genes expression of GABAergic and glutamatergic markers (Ma et al 2016;Zhang et al 2018;Silva et al 2019). An alternative hypothesis is that a-and c-tDCS may respectively activate and inactivate glial astrocytes, as reported recently (Monai et al 2016), which can exert differential influence on GLU and GABA syntheses by affecting the GLN-GLU/GABA metabolic cycle (Jacob et al 2014;Walls et al 2015;Zheng et al 2016;Albrecht & Zielińska, 2017).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Interestingly, a 24 h activity-deprivation paradigm in cultured hippocampal neurons using non-competitive antagonists of AMPARs and NMDARs (GYKI-52466 and MK-801, respectively) does not affect miR-92a or miR-124 levels but rather downregulates miR-186-5p, a miRNA which also targets GluA2, thereby leading to the synaptic insertion of GluA2-containing AMPARs which are not permeable to calcium (Silva et al, 2019). Finally, a 24–48 h treatment with TTX alone induces the insertion of GluA2-containing AMPARs (Sutton et al, 2006; Gainey et al, 2009), but a specific regulation of this process by miRs has not been reported yet.…”
Section: Mirna-dependent Control Of Post-synaptic Function During Hommentioning
confidence: 99%